Exploring financial distress through Altman Z” score: example of selected private commercial banks in Nepal - Gyawali, Santosh (Journal of Emerging Management Studies, 2023)
Purpose - This research aims to explore the financial distress of selected Nepalese commercial banks using Altman’s Z” score model. Design/methodology/approach - Based on quantitative research approach, this research has followed descriptive research design to assess financial distress. Amid of 24 private commercial banks, this study has selected 16 sample banks conveniently. Altman’s revised Z” score (1993) model has been used to draw inferences. The published annual financial report of respective banks of year 2019-20 was employed as secondary information. Findings and Conclusion - Among 16 sampled banks, 6 commercial banks are laid under zone of distress and 10 banks as in undecided zone. Similarly, this study has revealed the inefficiency of Z” score model in predicting financial distress. Originality/value - Commencing Altman’s Z” score model designed for non-manufacturing and companies of emerging market in relation to Nepalese commercial banks.